2018
DOI: 10.1007/s00604-018-2737-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual and colorimetric determination of H2O2 and glucose based on citrate-promoted H2O2 sculpturing of silver nanoparticles

Abstract: Isotropic silver nanoparticles (iAg NPs) can be easily prepared at low costs, have a low electrochemical potential and high extinction coefficient. An effective colorimetric assay for HO is reported here based on the finding that HO can induce the shape transformation of citrate-capped iAg NPs with the help of citrate. The substantial shape variation affords an apparent surface plasmon resonance (SPR) shift, accompanied by a vivid color change from light yellow to mauve. The color change can be observed visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…However, the findings of this study suggest that these two peaks might be caused by different oxidation states, with no size change. A number of groups who used NC/NPs as glucose sensors saw an irreversible PL/absorbance shift or quenching caused by NC/NPs agglomeration or disintegration [20,23,30,31]. In contrast, the Ag NCs in this study had a reversible PL change, which is advantageous for use as a cheaper, reusable sensor.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…However, the findings of this study suggest that these two peaks might be caused by different oxidation states, with no size change. A number of groups who used NC/NPs as glucose sensors saw an irreversible PL/absorbance shift or quenching caused by NC/NPs agglomeration or disintegration [20,23,30,31]. In contrast, the Ag NCs in this study had a reversible PL change, which is advantageous for use as a cheaper, reusable sensor.…”
Section: Resultsmentioning
confidence: 76%
“…The response was similar to measurements using glucose in water. It was assumed that GOx was specific for glucose over other blood components due to measurements by Zong et al that had already shown this specificity [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biosynthesized nanoclusters exhibited ultrasensitive and selective detection of H 2 O 2 . The novelty of the reported method for the detection of H 2 O 2 , in comparison with previously reported methods, is presented in a tabulated form in Table 1 [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The biosynthesis of palladium nanoclusters in itself is a novel achievement, and no reports are available on the use of biological methods for this purpose.…”
Section: Introductionmentioning
confidence: 99%